Alma's Rainbow [videorecording (DVD)] - Chenzira, Ayoka; Weston-Moran, Kim; Nunes, Mizan; Dobson, Lee; Platt, Victoria, 1972-; Bourelly, Jean-Paul (Milestone cinematheque., 2022)
Rainbow is the daughter of Alma, the no-nonsense owner of a popular beauty parlor. Ruby, Alma's free-spirited sister, unexpectedy arrives after a ten year absence, causing Rainbow to confront her own sexual awakening and provoking Alma to reconsider her own self-inflicted repression.